Study on the Chemical Composition of Millettia Speciosa Roots - Duc Loi, Vu; Thi Hien, Nguyen; Thi Hong Nhung, Tran; Minh Thai, Nguyen; Thi Mai, Nguyen; Thi Minh Hai, Pham (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 38 No 3, 2022)
Abstract: Vietnam possesses an extremely abundant and diverse ecosystem with many species of plants used for medicinal purposes. Millettia speciosa Champ. is a plant of the Fabaceae family that is effective in arthritis, rheumatoid arthritis, amenorrhea, hepatitis, tuberculosis, and chronic bronchitis. However, so far, the studies on this species in the world as well as in Vietnam are relatively few. In this study, four compounds that were extracted and isolated from the aqueous extract of the roots of  Millettia speciosa  collected in Tuyen Quang province include maackiain, calycosin, genistein, and medicarpin. Their structures were elucidated by measuring the melting point, mass spectrometry, and nuclear resonance spectrum. Keywords: Millettia speciosa, maackiain, calycosin, genistein, medicarpin.